2022
DOI: 10.1021/acsapm.1c01205
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Groups Enable Electrosynthesized Polyfluorenes to Specifically Recognize Cr2O72–

Abstract: The unique “molecular wire effect” property of conjugated polymers (CPs) enables them to own signal amplification. Therefore, they are good candidates for constructing fluorescent sensors with high sensitivity. In this work, two water-soluble polyfluorene derivatives P­(Fmoc-Arg-OH) and P­(Fmoc-Glu-OH) were synthesized using electrochemical polymerization in boron trifluoride diethyl etherate–trifluoroacetic systems. Absorption and emission spectra showed that the two polymers were blue emitters. In order to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…As shown in Figure 2, as the number of scan cycles increased, the current density of a pair of reversible redox peaks in cyclic voltammograms (CVs) increased, indicating that monomers Fmoc-Ala-OH and Fmoc-Thr-OH can be electropolymerized in BFEE. By analysing the 1 H NMR spectra (Figures S1 and S2), it was found that two molecules were polymerized at the position 2,7, which was the same as other fluorene derivatives [13][14][15]31]. From GPC results, polymers P(Fmoc-Ala-OH) and P(Fmoc-Thr-OH) contained 72 and 41 repeat units, respectively.…”
Section: Electropolymerization Of Monomers Fmoc-ala-oh and Fmoc-thr-ohmentioning
confidence: 72%
See 3 more Smart Citations
“…As shown in Figure 2, as the number of scan cycles increased, the current density of a pair of reversible redox peaks in cyclic voltammograms (CVs) increased, indicating that monomers Fmoc-Ala-OH and Fmoc-Thr-OH can be electropolymerized in BFEE. By analysing the 1 H NMR spectra (Figures S1 and S2), it was found that two molecules were polymerized at the position 2,7, which was the same as other fluorene derivatives [13][14][15]31]. From GPC results, polymers P(Fmoc-Ala-OH) and P(Fmoc-Thr-OH) contained 72 and 41 repeat units, respectively.…”
Section: Electropolymerization Of Monomers Fmoc-ala-oh and Fmoc-thr-ohmentioning
confidence: 72%
“…In other words, the two polymers have high polymerization degrees. Combined with other polyfluorene reported by our groups [12][13][14][15], the shorter side chain groups will reduce the polymerization hindrance of fluorene. Importantly, high polymerization degrees are beneficial to the detection sensitivity in application.…”
Section: Electropolymerization Of Monomers Fmoc-ala-oh and Fmoc-thr-ohmentioning
confidence: 77%
See 2 more Smart Citations
“…49 Recently they have been explored in the Cr(VI) detection. 13,50 Yet detailed optical sensing mechanistic insights and affordable sensing platforms like paper test strips remain quite challenging. Herein, we report the synthesis of a water-soluble conjugated polyelectrolyte PPMI and its application as a fluorescence sensor for the detection of carcinogenic Cr(VI) in aqueous media and on a solid support.…”
Section: Introductionmentioning
confidence: 99%